Explanation :
$ \begin{array}{l}{\mathrm V}_0=\left[\frac{\mathrm R(1+\mathrm x)}{\mathrm{PR}+\mathrm R(1+\mathrm x)}-\frac{\mathrm R}{\mathrm R+(\mathrm{PR})}\right]\mathrm E\\{\mathrm V}_0=\left[\frac{\mathrm R(1+\mathrm x)}{\mathrm R+(1+\mathrm x+\mathrm P)}-\frac{\mathrm R}{\mathrm R+(1+\mathrm P)}\right]\mathrm E\\{\mathrm V}_0=\left[\frac{1+\mathrm x}{1+\mathrm x+\mathrm p}-\frac1{1+\mathrm P}\right]\mathrm E\\{\mathrm V}_0=\left[\frac{(1+\mathrm x)(1+\mathrm P)-(1+\mathrm x+\mathrm P)}{(1+\mathrm x+\mathrm P)(1+\mathrm P)}\right]\mathrm E\\{\mathrm V}_0=\left[\frac{1+\mathrm x+\mathrm{Px}+\mathrm P-1-\mathrm x-\mathrm P}{(1+\mathrm P+\mathrm x+\mathrm{xP}+\mathrm P+\mathrm P^2)}\right]\mathrm E\\\;\;\;\;\;=\left[\frac{\mathrm{Px}}{1+2\mathrm P+\mathrm P^2+\mathrm x+\mathrm{xP}}\right]\mathrm E\end{array} $
For maximum $ {\mathrm V}_0 $,
$ \frac{{\mathrm{dV}}_0}{\mathrm{dP}}=0 $
So, $ \frac{(\mathrm x)}{1+\mathrm x+\mathrm P(\mathrm P+2+\mathrm x)}-\frac{\mathrm{xP}\left\{2\mathrm P+\mathrm x+2\right\}}{(1+\mathrm x+\mathrm P(2+\mathrm P+\mathrm x))^2}=0 $
So, $ \left[1+\mathrm x+\mathrm P(2+\mathrm P+\mathrm x)\right]=\mathrm P(2\mathrm P+\mathrm x+2) $
$ \begin{array}{l}\Rightarrow\;1+\mathrm x+2\mathrm P+\mathrm P^2+\mathrm{px}=2\mathrm P^2+\mathrm{Px}+2\mathrm P\\\Rightarrow\;1+\mathrm x=\mathrm P^2\end{array} $
So, $ \mathrm P=\sqrt{1+\mathrm x} $